Lifetime Earnings Inequality in Germany - Bönke, Timm; Corneo, Giacomo; Lüthen, Holger (Journal of Labor Economics, 2015)
We employ German social security records to investigate intragenerational lifetime earnings inequality and mobility of yearly earnings for 35 cohorts, starting with the birth year 1935. Our main result is a striking secular rise of intragenerational inequality in lifetime earnings: West German men born in the early 1960s are likely to experience about 85% more lifetime inequality than their fathers. In contrast, both short-term and long-term intragenerational mobility are stable. Longer unemployment spells of workers at the bottom of the distribution of younger cohorts contribute to explaining 20%–40% of the overall increase in lifetime earnings inequality.